Muscle Dysfunction in Smokers and Patients With Mild COPD: A SYSTEMATIC REVIEW. Issue 4 (July 2019) - Fonseca, Jéssica; Nellessen, Aline Gonçalves; Pitta, Fabio
Abstract : Purpose: To describe and discuss the available evidence in the literature concerning muscle function and the association between smoking and muscle dysfunction in smokers and patients with mild chronic obstructive pulmonary disease (COPD). Methods: The literature search involved the following databases: PubMed, Pedro, CINAHL, Cochrane Library, Lilacs, and EMBASE. Studies were included if they investigated muscle strength and/or endurance and/or cross-sectional area (CSA) in smokers and/or patients with COPD classified as Global Initiative for Obstructive Lung Disease (GOLD) I and without lung cancer. Two authors screened and identified the studies for inclusion. Results: Eighteen studies were identified. Some studies found lower values in a variety of muscle strength variables in smokers compared with nonsmoking controls, whereas others found similar values between these groups. When comparing patients with COPD classified as GOLD I with smokers, COPD patients showed lower muscle strength. Two studies found no differences in muscle CSA between smokers compared with nonsmoking controls. Some preliminary evidence also shows that patients with COPD classified as GOLD I had lower CSA in comparison with smokers. Conclusion: Results concerning muscle dysfunction in smokers are divergent, since some studies have shown worse results in a variety of muscle strength variables in smokers compared with nonsmoking controls, whereas other studies have not. Moreover, there is rather preliminary evidence indicating worse muscle dysfunction and lower CSA in patients with mild COPD in comparison with healthy (or non-COPD) smokers. Abstract : This review describes and discusses the available evidence about the association between smoking and muscle dysfunction in smokers and patients with mild COPD. Results showed that there is still insufficiently clear evidence about the presence and characteristics of muscle dysfunction when comparing smokers versus nonsmokers and smokers versus patients with mild COPD.